Safety, cost effectiveness and experience of day care laparoscopic cholecystectomy: a report from a tertiary care center - Khemchand, Agrawal Kavita; Singh, Kaptan; Kaman, Lileswar; Dahiya, Divya; Behera, Arunanshu (International Surgery Journal, 2020)
Background: Laparoscopic cholecystectomy is the recommended standard of care for symptomatic gall stone disease. We report our experience of day care laparoscopic cholecystectomy in terms of safety, feasibility and cost factor. Methods: A retrospective analysis was performedon data collected from June 2014 to December 2018 from a single unit at PGIMER, Chandigarh, India. Patients who were graded I and II on the ASA score, accompanied by at least one attendant and able to come to hospital by their own arrangements in case of any problem wereselected for day care laparoscopic cholecystectomy. Results: Out of 1054, 826 (78.4%) were female and 228 (21.6%) were male patients. Mean age of the study cohort is 43.3 years with minimum and maximum age being 13 and 80 years respectively. GSD with chronic cholecystitis were present in maximum number of patients (875, 83.01%) and GSD with chronic liver disease in minimum number of patients (5, 0.47%). There was no common bile duct injury. A total of 9 (0.85%) patients got converted to open surgery requiring admission. There was no mortality. On evaluating the cost factor, cost saving of Rs. 8200/- was found between DCLC group and private ward patients while of Rs. 365/- between DCLC group and general ward patients. Conclusion: Day care laparoscopic cholecystectomy is safe in carefully selected patients and has the advantage of cost factor. This will help us in increasing patient turnover and thus reducing waiting time for wait listed patients.